Dataset for AABS baseline/characterization in Kenya (wp2) - Brako Dompreh, Eric; Zewdie, Markose; Manyise, Timothy; Chelanga, Philemon; Kangogo, Daniel (2025)
In October 2024, data were collected from 739 mariculture and seaweed farmers across target counties in Kenya through computer-assisted personal interviews (CAPIs) conducted on mobile tablets by 28 trained enumerators. A KoBo-based questionnaire was utilized. Multistage sampling was employed to select farmers and value-chain stakeholders. This study is part of a new project called the Asia Africa Bluetech Superhighway project, aimed to understand practices, including farmed species and their environmental impact. The project focuses on testing and expanding Integrated Multi-Trophic Aquaculture (IMTA) in coastal Kenya, an approach that involves farming diverse species like fish, shellfish, and seaweed together to enhance environmental health and be beneficial to farmers.